2022
DOI: 10.1063/5.0079011
|View full text |Cite
|
Sign up to set email alerts
|

Highly stable PEDOT:PSS electrochemical transistors

Abstract: Organic electrochemical transistors (OECTs) are a burgeoning biosensing transducer platform due to their intrinsic amplification, high transconductance, and biocompatibility. To be successful in real world biosensing applications, however, stable performance should be demonstrated to avoid false analyte readings that could lead to dangerous misdiagnosis. This work demonstrates the stability of carefully prepared OECTs using commercially available PEDOT:PSS as the channel layer. These devices exhibit more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…These results show that PEGDE crosslinked PEDOT:PSS thin films exhibit superior electrochemical properties compared with GOPS crosslinked PEDOT:PSS thin films. However, we should note that the typical PEDOT:PSS crosslinking formulation that is used for thin bioelectronic devices is GOPS (1 wt%), 20 with electrical conductivity values in the range of 400 S/cm 24 and volumetric capacitance of 39 F/cm 3 . 32 We found that the OECT transconductance (gm) is higher for PEDOT:PSS channels crosslinked with PEGDE (3 wt%) compared with PEDOT:PSS channels crosslinked with the standard GOPS (1 wt %) (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results show that PEGDE crosslinked PEDOT:PSS thin films exhibit superior electrochemical properties compared with GOPS crosslinked PEDOT:PSS thin films. However, we should note that the typical PEDOT:PSS crosslinking formulation that is used for thin bioelectronic devices is GOPS (1 wt%), 20 with electrical conductivity values in the range of 400 S/cm 24 and volumetric capacitance of 39 F/cm 3 . 32 We found that the OECT transconductance (gm) is higher for PEDOT:PSS channels crosslinked with PEGDE (3 wt%) compared with PEDOT:PSS channels crosslinked with the standard GOPS (1 wt %) (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…3-glycidyloxypropyl)trimethoxysilane (GOPS) is the most commonly used crosslinker 18 and leads into PEDOT:PSS structures with adequate stability in cell-culture conditions for a variety of bioelectronic applications. 19,20 Alternative crosslinking strategies involve the use of poly(ethylene glycol)diglycidyl ether (PEGDE) 21 and divinyl-sulfone (DVS). 22 Both GOPS and PEGDE render PEDOT:PSS water-stable via similar mechanisms — a reaction of the epoxy rings moiety present in their structures with the weakly nucleophilic PSS - .…”
Section: Introductionmentioning
confidence: 99%
“…The sacrificial PaC layer was peeled off, and the samples were hard-baked to cross-link the PEDOT:PSS. Last, the samples were soaked in deionized water overnight and preconditioned to maximize stability ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…The sacrificial PaC layer was peeled off and the samples were hard-baked to cross link the PEDOT:PSS. Finally, the samples were soaked in DI water overnight and preconditioned to maximize stability (22). OECT measurements were collected using a Keysight B1500A semiconductor device analyzer.…”
Section: Methodsmentioning
confidence: 99%